Intraventricular CNS lesions: A pictorial essay. Issue 4 (2nd March 2015) - Watts, Jane; Yap, Kelvin K; Ou, Daniel; Tartaglia, Con; Trost, Nicholas; Sutherland, Tom
Summary Intraventricular lesions of the central nervous system (CNS) can present a diagnostic challenge due to a range of differential diagnoses and radiological appearances. Both CT and MRI imaging findings, in combination with location and patient's age, can help limit the differentials. This pictorial essay presents the salient radiological features, location and demographics of the more common intraventricular lesions of the brain.